‘Super Rehab’: can we achieve coronary artery disease regression? A feasibility study protocol - David Murphy; Charalambos Antoniades; John Graby; Fiona Gillison; Amardeep Dastidar; Dylan Thompson; Theresa Smith; Oliver Peacock; Ali Khavandi; Hugh McLeod; Jonathan Carl Luis Rodrigues (BMJ Open)
Introduction Patients diagnosed with coronary artery disease (CAD) are currently treated with medications and lifestyle advice to reduce the likelihood of disease progression and risk of future major adverse cardiovascular events (MACE). Where obstructive disease is diagnosed, revascularisation may be considered to treat refractory symptoms. However, many patients with coexistent cardiovascular risk factors, particularly those with metabolic syndrome (MetS), remain at heightened risk of future MACE despite current management.Cardiac rehabilitation is offered to patients post-revascularisation, however, there is no definitive evidence demonstrating its benefit in a primary prevention setting. We propose that an intensive lifestyle intervention (Super Rehab, SR) incorporating high-intensity exercise, diet and behavioural change techniques may improve symptoms, outcomes, and enable CAD regression.This study aims to examine the feasibility of delivering a multicentre randomised controlled trial (RCT) testing SR for patients with CAD, in a primary prevention setting.Methods and analysis This is a multicentre randomised controlled feasibility study of SR versus usual care in patients with CAD. The study aims to recruit 50 participants aged 18–75 across two centres. Feasibility will be assessed against rates of recruitment, retention and, in the intervention arm, attendance and adherence to SR. Qualitative interviews will explore trial experiences of study participants and practitioners. Variance of change in CAD across both arms of the study (assessed with serial CT coronary angiography) will inform the design and power of a future, multi-centre RCT.Ethics and dissemination Ethics approval was granted by South West—Frenchay Research Ethics Committee (reference: 21/SW/0153, 18 January 2022). Study findings will be disseminated via presentations to relevant stakeholders, national and international conferences and open-access peer-reviewed research publications.Trial registration number ISRCTN14603929.